O museu Julio de Castilhos no período 1960-1980: acervos, discursos, representações e práticas através de uma exposição museológica - Silveira, Andréa Reis da (2011)
The current paper aims to focus a museum exhibition developed from the investigation about the history of Júlio de Castilhos Museum from 1960 to 1980. The museum speeches and the performances that determined the museum imagination about its history and also about its symbols were assessed in the research. The history of Júlio de Castilhos Museum from 1960 until 1980, which used to be unknown until these days, has become object of evaluation by the museum historical field and by the subjects who manage the institution. These members have been politically linked to the museum and influenced by a historical and political context. It has made this museum a historical one. By analyzing and exhibiting the museum collections at that time, it was perceived a permanent game between the memory will and the intention of reflecting its history. What happened at Júlio de Castilhos Museum from 1960 until 1980 can be seen under the view of the imprecision of a museum, estate and cultural policy from ideological federal and state instances. This is apparent when there is a discussion about the frequent line changes of the activities developed by the museum as its managers changed. It was also noticed when there were losses or imminent losses of entire collections of weapons or other items due to negligence or default. This institution has been closed many times because of infra-structure problems like lack of financial resources and investments occluded by media and populist events. This is the history shown in the exhibition.